(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE To determine the outcomes of tamsulosin in women with lower urinary tract symptoms among patients presenting at tertiary care hospital in Pakistan. METHODOLOGY This descriptive study was carried out at the Sindh Institute of Urology & Transplantation (SIUT) in Karachi from September 2023 to March 2024. A total of 97 women aged between 18 and 60 years were included using a non-probability consecutive sampling technique. Each participant was administered Tamsulosin 0.4 mg once daily. The uroflowmetry (UFM) and American Urological Association (AUA) symptom score were recorded both at baseline and after six weeks.The effectiveness of Tamsulosin was evaluated by comparing pre-and post-treatment values of QMax (maximum flow rate), residual urine volume, and International Prostate Symptom Score (IPSS). Data analysis was performed using SPSS version 26.0, and a p-value of less than 0.05 was considered statistically significant. RESULTS The mean ± standard deviation of the age was found as 47.80 ± 10.34 years. Tamsulosin significantly improved IPSS scores (16.83 ± 5.61 vs. 12.94 ± 6.52, p=0.0001), voiding symptoms score (10.82 ± 2.82 vs. 6.88 ± 2.17, p=0.0001), storage symptoms score (5.46 ± 1.70 vs. 4.54 ± 1.19, p=0.0001), residual urine volume (62.52 ± 17.46 vs. 31.94 ± 7.30 mL, p=0.0001), and QMax flow rate (15.33 ± 7.02 vs. 17.31 ± 5.36 mL/sec, p=0.039). However, the mean flow rate showed no significant change (p=0.225). CONCLUSION Tamsulosin presents a new beneficial treatment option for women with LUTS, providing a significant reduction in symptom severity and urinary flow. The drug was well tolerated and induced a significant reduction of voiding and storage symptoms. Tamsulosin could be an alternative treatment for LUTS in women because of its efficacy and good safety profile. More studies are needed to prove that its effects last and what are the ideal treatment protocols.